2020
DOI: 10.1101/2020.08.31.263319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of Lyme disease on treeless islands in Scotland, UK

Abstract: Lyme disease (LD) is typically associated with forested habitats but has recently emerged on treeless islands in the Western Isles of Scotland. This has created a need to understand the environmental and human components of LD risk in open habitats. This study quantified both elements of LD risk and compared these between treeless islands with high and low LD incidence. We found high LD incidence was linked to higher prevalence in ticks (6.4% vs 0.4%) and increased human tick bite exposure. Most reported tick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The small spatial scale of our plots, while a potential issue for con rming a link between rodent abundance and NIP, proved su cient to demonstrate effects of high deer density on DON, vegetation height and rodent activity, and ultimately, Lyme disease hazard. While a previous meta-analysis of deer exclusion effects on tick abundance (14) suggested that deer exclusion areas of at least 2.5 ha may be necessary to have an effect, our results show smaller plots sizes to be su cient for revealing strong spatial gradients and for testing impacts of deer on ticks, consistent with other more recent studies (Gilbert et Irrespective of the mechanisms driving NIP, the most critical parameter governing public health and policy importance for Lyme disease is the density of infected nymphs (DIN=NIP x DON), which is the key proxy for Lyme disease hazard in the environment (29). DIN was ve times higher in high deer density plots compared to exclosures due to deer having a strong positive effect on DON.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The small spatial scale of our plots, while a potential issue for con rming a link between rodent abundance and NIP, proved su cient to demonstrate effects of high deer density on DON, vegetation height and rodent activity, and ultimately, Lyme disease hazard. While a previous meta-analysis of deer exclusion effects on tick abundance (14) suggested that deer exclusion areas of at least 2.5 ha may be necessary to have an effect, our results show smaller plots sizes to be su cient for revealing strong spatial gradients and for testing impacts of deer on ticks, consistent with other more recent studies (Gilbert et Irrespective of the mechanisms driving NIP, the most critical parameter governing public health and policy importance for Lyme disease is the density of infected nymphs (DIN=NIP x DON), which is the key proxy for Lyme disease hazard in the environment (29). DIN was ve times higher in high deer density plots compared to exclosures due to deer having a strong positive effect on DON.…”
Section: Discussionsupporting
confidence: 90%
“…These different mechanisms are not mutually exclusive and the effect of high deer density on NIP will depend on the relative strength of the rst (transmission potential) mechanism compared to the other two (dilution and ecological cascade mechanisms) (Figure 1). A further key aim was to test the impact of high deer density on Lyme disease hazard, which is de ned as the density of infected nymphs (DIN) in the environment and is the product of NIP and DON (29). It is di cult to predict the effect of deer on Lyme disease hazard because it will depend on the relative strengths of the effect of deer on DON and the mechanisms driving NIP (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…genospecies were found in all years, at both sites, with a minimum overall prevalence of 12.6%. This compares with overall Borrelia prevalences of I. ricinus of 1.7% (range 0–6.0%) detected in questing nymphs sampled at multiple sites across mainland Scotland and the Isle of Mull [ 25 ], 6.4% and 0.7% in questing nymphs at sites of, respectively, high and low Lyme disease incidence in the Outer Hebrides [ 26 ], 3.2% (range 0–5.6%) in questing nymphs and adults at four sites in England [ 27 ], 19.0% (range 0–24.5%) in questing nymphs collected over three years at sites in a single area of southern England [ 28 ] and 3.8% (range 0–24.0%) in questing ticks collected over six years at 20 sites in recreational areas of England and Wales [ 29 ]. In the two last-mentioned studies, significant variation was seen in tick infection rates between years [ 28 , 29 ]; on Brownsea Island, where ticks were sampled in both Spring and Autumn, the minimum overall prevalence of Borrelia infection was 9.9% in 2017 compared with 21.3% in 2018.…”
Section: Discussionmentioning
confidence: 84%
“…Irrespective of the mechanisms driving NIP, the most critical parameter governing public health and policy importance for Lyme disease is the DIN (= NIP × DON), which is the key proxy for Lyme disease hazard in the environment [29]. DIN was five times higher in high deer density plots compared to exclosures due to deer having a strong positive effect on DON.…”
Section: Discussionmentioning
confidence: 99%
“…1). A further key aim was to test the impact of high deer density on Lyme disease hazard, which is defined as the DIN in the environment and is the product of NIP and DON [29]. It is difficult to predict the effect of deer on Lyme disease hazard because it will depend on the relative strengths of the effect of deer on DON and the mechanisms driving NIP (Fig.…”
Section: Introductionmentioning
confidence: 99%